EFEKTIVITAS PEMBERIAN SNACK BAR TAPE KETAN HITAM TERHADAP POLA DEFEKASI IBU NIFAS - Yanti, Risna Dewi (Ikatan Bidan Indonesia (IBI), 2022)
The digestion of puerperium experience physiology change that have an impact to difficukty of defecation. this is caused by intestial muscle tone decrease during labor and early of puerperium, diarrhea before labor, eating irregularly, dehydration , hemorrhoids or laceration of the birth canal. feeding food that contains high fiber for smooth defecation so that can prevent constipation to mother in postpartum considered quite effective. the fiber of the food has ability to binding water in colon to make feces volume being bigger and to stimulate nerves in the rectum so can rise the desire to defecation. so therefore feces easier to elimination. proven influence is increasing the feces volume, soften the consistency of feces and shorten timing of intestinal transit. one of fiber source food is tape black sticky rice 5,9 gram/100 gram. the purpose of this research is to knowing the the effectiveness of giving the snack bar black tape sticky rice to pattern of postpartum maternal defecation. This research use the research desain of quadi experiment (two group post design) to know the influence by giving the snack bar tape black sticky rice to pattern of postpartum maternal defecation. the place of this research is in bogor city, held on february-october 2019 with the sample of postpartum mother a number of 30 persons for each group with the total sample of 60 persons. The bivariat analysis carried out the test mannwhitney. the result of this data there is the significant difference by giving the snack black tape sticky rice bar to pattern of postpartum maternal defecation with score p=0,00. the conclusion of this research is giving the snack black tape sticky rice bar is effective to pattern of defecation.